ANALISIS FAKTOR-FAKTOR DETERMINAN DALAM UPGRADING PERAN THIRD PARTY LOGISTICS (3PL) MENJADI FOURTH PARTY LOGISTICS (4PL) PADA PERUSAHAAN LOGISTIK DI KABUPATEN GRESIK - Nanda Aprilia Rahma; Abi Hanif Dzulquarnain (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to identify and analyze the determinant factors that influence the need for upgrading logistics services from Third Party Logistics (3PL) to Fourth Party Logistics (4PL) at a logistics company in Kabupaten Gresik, East Java, which manages around 94 warehouse branches and more than 400 transportation fleets across Indonesia. This research applies a mixed-method approach combining descriptive qualitative analysis with quantitative survey data. Data were collected from 100 respondents directly involved in the company's logistics operations and processed using Exploratory Factor Analysis (EFA) with Principal Component Analysis extraction and Varimax rotation through IBM SPSS Statistics, preceded by validity testing (Pearson item-total correlation) and reliability testing (Cronbach's Alpha). The results show that out of 30 initial indicators, 27 were valid, and after iterative screening based on Measure of Sampling Adequacy (MSA), 20 indicators remained eligible for further analysis, with a final KMO value of 0.627 and Cronbach's Alpha of 0.761. Seven factors were extracted, jointly explaining 60.909% of total variance: Technological Readiness and Human Resource Competence, Distribution Operational Planning and Control, Infrastructure Readiness and Fleet Planning, Distribution Network Integration and Leadership Role, Strategic Readiness and Supply Chain Visibility, Logistics Data Reliability and Synchronization, and Technology Development Commitment and Policy Support. Technological Readiness and Human Resource Competence was identified as the most dominant factor, contributing 16.263% of total variance, indicating that technological investment must be balanced with workforce competence to support the company's transformation from 3PL to a more integrated 4PL model.